Konteks Pembentuk Wacana Pacifism dalam Anime Hotaru no Haka karya Isao Takahata - Dana, Pande Krisna; Ari Sulatri, Ni Luh Putu; Anggraeny, Renny (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 1 (2021), 2021)
The tittle of this research was “ Forming Context of Pacifism  Discourse in Hotaru no Haka anime by Isao Takahata ”. The purpose of this research to find out the forming context of pacifism discourse in Hotaru no Haka anime by Isao Takahata. Data colletion method in this research was literature study method.   The data were analyzed by using descriptive analysis method and informal method. The theory applied in this research was critical discourse analysis by Van Dijk (1988). The result in this research were 1) novelist and anime director are victims of war; 2) prohibition of war in article 9 of the Japanese Constitution and; 3) Japan signed the treaty of San Francisco.